Hematological Profiles in Hemoglobinopathy Patients in South Western Nepal - Gautam, Narayan; Jayan, Archana; Dubey, Raju Kumar; Jha, Amit Chandra; Deshar, Sunkeshari; Tamang, Binaya; Pokhrel, Buddhi Raj; Phuyal, Reena; Shah, Anita; Kaphle, Raju (Journal of Universal College of Medical Sciences, 2020)
INTRODUCTION: Homozygous inheritance of the hemoglobin results in sickle cell anemia (SCA), heterozygous inheritance results in sickle cell trait (SCT). Sickle cell anemia and β-thalasemia (β-TT) have been a major health threat for the tharu living in the South-Western Terai of Nepal. This study is carried out to apply and optimise the phenotypic method and haematological profile to characterise the SCT, SCA and β-TT from suspected tharu community dwellers. MATERIAL AND METHODS: We enrolled 100 suspected cases of hemoglobinopathies of 12-14 years children and ≥15 years adults tharu community dwellers from Dang, Kapilvastu, Nepalgunj, Rupandehi and Nawalparasi of South-Western Nepal from May 2018 to November 2018. Five mililitre of blood was collected in EDTA vial and transported to the laboratory maintaining cold chain. The hematological profile was recorded after investigations. The hemolysate from blood samples were subjected to phenotypic testing by adopting cellulose acetate electrophoresis at pH 8.6. RESULTS: Our result showed the commonest hemoglobinopathy was SCT (38%) followed by β-TT (21%) and SCA (5%). Males were more affected with SCA (60%) while that of females were most affected with β-TT (57.1%). Only 44.7% females were affected with SCT while 42.9% males were affected with β-TT. The significant difference in mean was observed in Hb level (p=0.0001), RBC (p=0.004), MCHC (p=0.015) and RDW (p=0.028) whereas the non-significant difference in mean was observed for glucose 6 phosphate dehydrogenase (G6PD) level (p=0.063) in hemoglobinopathy patients. CONCLUSION: Most cases develop severe type of anemia as shown by change in hematological parameters. This information could advocate for timely counselling before constellation of associated condition appeared in hemoglobinopathy patients.